Development of the mutual influence model of laser gyroscope dithers in sins - Іванов, Сергій Вікторович; Воловик, Богдан Васильович; Слабухін, Ігор Сергійович (Eastern-European Journal of Enterprise Technologies, 2015)
The problem of the mutual influence of laser gyroscope dithers in SINS is underinvestigated. No other author has developed the model of the processes, occurring in the SU (sensing unit) during interaction of dithers, which would allow to examine the unit operation at the complex vibration of dithers and take into account the design features of real SINS. In the paper, the general structure of the mutual influence mathematical model of laser gyroscope dithers in SINS was obtained, and the parameters of the model for a real unit were identified. The mathematical model allows to evaluate linear and angular displacements of each LG (laser gyroscope) from internal vibroimpacts, including a noise component during the SINS SU operation. Knowing the displacement data, SU systematic errors, including conical motion error and measurement axes displacement error can be estimated. The model significantly reduces the simulation time compared to simulations using the finite element method. The work can be used as a guide for obtaining and identifying the mutual influence model of several physical bodies placed on one elastic object.